Strengthened floatation of molybdite using oleate with suitable co-collector. (15th June 2018) - Wang, Zhen; Wang, Li; Wang, Jinming; Xiao, Junhui; Liu, Jian; Xu, Longhua; Fu, Kaibin
Graphical abstract: DDA can be adsorbed between the adjacent pre-adsorbed NaOl ions, while CPC cannot due to its big headgroup. Adsorption model of Mixed NaOl/CPC and NaOl/DDA on molybdite. Highlights: The collecting ability for molybdite is in the sequence of NaOl > CPC > DDA. The best flotation recovery is reached with mixed NaOl/DDA. DDA is adsorbed on molybdite surface with monolayer adsorbed NaOl. CPC cannot be adsorbed on molybdite surface with monolayer adsorbed NaOl. Abstract: The difference in flotation and adsorption mechanism of mixed sodium oleate (NaOl)/dodecylamine (DDA) and NaOl/cetyl pyridinium chloride (CPC) collectors on molybdite was comparative studied through micro-flotation, fluorescence emission spectroscopy, zeta potentials measurement, adsorption tests and FTIR measurement. The flotation results show that the best flotation of molybdite for 2 × 10 −4 M NaOl, CPC and DDA is achieved at pH 7, 8 and 10, with corresponding mineral recovery of 64.3%, 40.9% and 44.5%, respectively. It is found that the collecting ability of single collector on molybdite is in the order of NaOl > CPC > DDA. For mixed system, molybdite recoveries with NaOl are improved by co-adsorbed DDA from about 75% to 95% with increasing DDA dosage, while no improvement is found in the case of mixed NaOl/CPC collectors. Fluorescence emission spectroscopy investigation displays the critical hemimicelle concentration (CHC) and critical micelle concentration (CMC) of NaOl are 2 × 10 −4 M and 2 × 10 −3 M, respectively. A larger micro-polarity of molybdite in mixed NaOl/DDA than that of mixed NaOl/CPC collectors is found. The adsorbed amount of DDA increase with the increasing DDA dosage due to the extra adsorption of DDA cations between the adjacent adsorbed NaOl ions, which leads to the less negative zeta potentials (from about −60 mV to −30 mV) of molybdite surface for mixed NaOl/DDA collectors. Above phenomenon and corresponding explanation are further confirmed by FTIR findings. Suggested models are presented to interpret the difference in adsorption mechanism of mixed NaOl/DDA and NaOl/CPC collectors on molybdite.